Apprenticeship : towards a new paradigm of learning - Ainley, Patrick; Rainbird, Helen (London : Kogan page, 1999)
"Apprenticeship: Towards a New Paradigm of Learning defines the contribution of work-based learning to the education and training of young people and focuses on the strengths of the apprenticeship system. It also extends the notion of apprenticeship from work and from higher education studentship to develop and explore different contexts for learning to challenge prevailing orthodoxies on the nature of learning."--BOOK JACKET. "Both critical and constructive, this book will be essential reading for anyone involved with apprenticeship, as well as for those concerned with approaches to learning and with widening participation in both education post-16 and work-based learning. In addition to researchers, academics, policy makers and students, it will be thought-provoking reading for training managers, trade unionists and those with an interest in learning policy and learning about learning."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Apprenticeship programs. -- Great Britain